2017
DOI: 10.3892/etm.2017.4813
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the osteogenic differentiation of gingiva-derived stem cells grown on culture plates or in stem cell spheroids: Comparison of two- and three-dimensional cultures

Abstract: Three-dimensional cell culture systems provide a convenient in vitro model for the study of complex cell-cell and cell-matrix interactions in the absence of exogenous substrates. The current study aimed to evaluate the osteogenic differentiation potential of gingiva-derived stem cells cultured in two-dimensional or three-dimensional systems. To the best of our knowledge, the present study is the first to compare the growth of gingiva-derived stem cells in monolayer culture to a three-dimensional culture system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Osteogenic differentiation was carried out in a number of studies by conducting GMSCs culture in osteoinductive medium with addition of dexamethasone, ascorbic acid, and β-glycerophosphate (among others) [22,25,28,29,32,[35][36][37]. The results of differentiation were confirmed with Alizarin Red S staining to detect calcified deposits in culture, alkaline phosphatase (ALP) activity assay, and gene expression analysis of bone specific markers-Runx2 (Runt-related transcription factor 2), collagen I, ALP, osteocalcin (OCN), and bone sialoprotein (BSP) [22,25,28,29,32,[35][36][37]. Moreover, GMSCs exhibited higher osteogenic potential than BM-MSCs, as indicated by Sun et al [36].…”
Section: Stemness Properties and Differentiation Ability Of Gmscsmentioning
confidence: 99%
“…Osteogenic differentiation was carried out in a number of studies by conducting GMSCs culture in osteoinductive medium with addition of dexamethasone, ascorbic acid, and β-glycerophosphate (among others) [22,25,28,29,32,[35][36][37]. The results of differentiation were confirmed with Alizarin Red S staining to detect calcified deposits in culture, alkaline phosphatase (ALP) activity assay, and gene expression analysis of bone specific markers-Runx2 (Runt-related transcription factor 2), collagen I, ALP, osteocalcin (OCN), and bone sialoprotein (BSP) [22,25,28,29,32,[35][36][37]. Moreover, GMSCs exhibited higher osteogenic potential than BM-MSCs, as indicated by Sun et al [36].…”
Section: Stemness Properties and Differentiation Ability Of Gmscsmentioning
confidence: 99%
“…Bone marrow is an attractive source of stem cells, but gaining stem cells from bone marrow may produce greater pain and morbidity [10]. Stem cells can also be achieved intraorally, and gingiva may serve as a more feasible source for stem cells because obtaining gingival-derived stem cells can be done under local anesthesia with less pain and morbidity [11]. Figure 1 shows morphology of the stem cells cultured in an alpha-minimal essential medium (α-MEM, Gibco, Grand Island, NY, USA) containing 15% fetal bovine serum (Gibco), 100 U/mL of penicillin, 100 μg/mL of streptomycin (Sigma-Aldrich Co., St. Louis, MO, USA), 200 mM of lglutamine (Sigma-Aldrich Co.), and 10 mM of ascorbic acid 2-phosphate (Sigma-Aldrich Co.) on Day 12.…”
Section: Characteristics Of Stem Cell Researchmentioning
confidence: 99%
“…In a previous report, two-and three-dimensional systems were used for the determination of secreted human vascular endothelial growth factor using a commercially available kit (Quantikine ® ELISA, R&D Systems, Inc., Minneapolis, MN, USA) [6]. The osteogenic differentiation of gingiva-derived stem cells grown on culture plates or in stem cell spheroids were evaluated by comparing two-and three-dimensional cultures, and the results indicated that gingiva-derived stem cell spheroids exhibit an increased osteogenic potential compared with stem cells from two-dimensional culture [11]. The co-culture of various cells including stem cells and primary cells can be done at various ratios [5].…”
Section: Secretion Of Growth Factors May Differ Between Two-dimensionmentioning
confidence: 99%
“…However, as the mechanisms of tumor progression and the tumor microenvironment have become elucidated, the limitations of the models have become increasingly apparent. Traditional two-dimensional (2D) cultures lack the diversity of internal spatial information, cell types, and the TME 15 . Although animal models can simulate physiological conditions and reflect interactions between various systems, clinical trials have had a low rate of success, requiring a long culture cycle, and are associated with high costs 16 .…”
Section: Introductionmentioning
confidence: 99%